2012
DOI: 10.1111/j.1365-3156.2012.02972.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to conducting effective obstetric audit in Ifakara: a qualitative assessment in an under‐resourced setting in Tanzania

Abstract: Abstractobjective To explore barriers to and solutions for effective implementation of obstetric audit at Saint Francis Designated District Hospital in Ifakara, Tanzania, where audit results have been disappointing 2 years after its introduction.methods Qualitative study involving participative observation of audit sessions, followed by 23 indepth interviews with health workers and managers. Knowledge and perceptions of audit were assessed and suggestions for improvement of the audit process explored.results D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(83 citation statements)
references
References 20 publications
7
76
0
Order By: Relevance
“…; van Hamersveld et al . ), attrition of staff (Nyamtema et al . ) and inadequate identification of sub‐standard care (Kidanto et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; van Hamersveld et al . ), attrition of staff (Nyamtema et al . ) and inadequate identification of sub‐standard care (Kidanto et al .…”
Section: Discussionmentioning
confidence: 99%
“…; van Hamersveld et al . ). The overall aim of this study was to explore the current implementation of MPDRs in Tanzania.…”
Section: Introductionmentioning
confidence: 97%
“…The issue of recommendations lies in the question of whether the recommendations will be acted upon and subsequently evaluated. Previous studies have shown that recommendations resulting from the audit sessions were poorly implemented because of a lack of human and material resources and insufficient staff and senior management commitment [13,14]. Conversely, in other studies where recommendations were implemented and evaluated, reductions in maternal mortality, the case fatality rate [50,51], the incidence of uterine rupture, obstetric hemorrhage and the number of women with severe maternal complications were observed [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, van Hamersveld and colleagues [14] explored barriers to implementing an obstetric audit at Saint Francis Designated District Hospital in Ifakara, Tanzania. They conducted participant observations and in-depth interviews with 23 healthcare workers who reported that audit sessions were only convened when the head of the department of obstetrics and gynecology was available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation